Cold tolerance of two Antarctic terrestrial arthropods - Block, William; Young, Stephen R; Conradi-Larsen, Else-Margrete; Sømme, Lauritz (Experientia, 1978)
Two Antarctic arthropods,Alaskozetes antarcticus (Acari) andCryptopygus antarcticus (Collembola) possess the ability to supercool to −30°C, but the realisation of this potential is dependent on starvation. The mite contains glycerol in a concentration of about 1% fresh weight.
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; virvelløse dyr

Cold-Hardiness of Cryptopygus antarcticus (Collembola) from Bouvetøya - Sømme, Lauritz (Oikos, 1978)
Cryptopygus antarcticus Willem were extracted from samples of mosses collected at Bouvetøya during the Norwegian Antarctic Expedition in February 1977. The body length of the collembolans from these samples ranged from 225 to 1125 μm. The collembolans had average supercooling points between -24° and -26°C. Acclimation at -5°, 0° and 12°C for various time intervals had no significant effect on their ability to supercool. Glycerol was not found in specimens acclimated at -5° and 0°C. All specimens were killed by freezing at temperatures in the range of their supercooling points. Chill-coma temperatures of the collembolans were between -2° and -7°C.
Keywords: Bouvetøya; NARE 1976/77; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Kuldetoleranse hos alpine og arktiske collemboler - Sømme, Lauritz (Entomologisk tidskrift, 1978)
Keywords: Antarktis; ekspedisjoner; entomologi; forskning; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Notes on the cold-hardiness of prostigmate mites from Vestfjella, Dronning Maud Land - Sømme, Lauritz (Norwegian Journal of Entomology, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; kuldetoleranse; midder; miter; virvelløse dyr; zoologi